North America Extratropical Cyclone (NAEC) Catalogue - Chen, Ting-Chen; Di Luca, Alejandro; Winger, Katja (Borealis, 2022)
The NAEC catalogue comprises information on extratropical cyclone (ETC) tracks in North America (20–80 N and 180-0W) from January 1979 to December 2020. The source data used to produce this dataset is obtained from the ECMWF ERA5 reanalysis at 1-hour spatial resolution and 0.25x0.25 degree spatial resolution. In addition to the location, time, and intensity, this dataset also includes ETC-associated impact variables such as the near-surface wind speed, wind gust, and precipitation, averaged using different radii around the ETC center. Both absolute and relative (to the local climatology) measures are provided. This catalogue provides useful information for the assessment of ETC-induced impacts over North America.

North America ISD to ERA5 (NA-ISD2ERA) Catalogue - Collet, François; Di Luca, Alejandro; Chen, Ting-Chen (Borealis, 2022)
The NA-ISD2ERA is a station-based gridded dataset of hourly 10-m wind speed, surface total precipitation, sea-level pressure, and 2-m air and dew point temperature observations interpolated on the regular 0.25° latitude-longitude ERA5 grid over North America for the 1990-2021 period. Station observations are from the Integrated Surface Database (ISD) developed by the National Centers for Environmental Information (NCEI) of the National Oceanic and Atmospheric Administration (NOAA) (Smith et al. 2011). It includes over 35,000 weather stations around the world of hourly to sub-hourly in situ observations for numerous variables such as wind speed, precipitation, sea-level pressure, air and dew point temperature. The NCEI ISD dataset is available at https://www.ncei.noaa.gov. ERA5 is the fifth generation of the European Centre for Medium-Range Weather Forecasts (ECMWF) reanalysis (Hersbach et al., 2020). Quality checks implemented in ISD are used to select reliable observations. For each ERA5 grid cell and at each hour, the data are interpolated by taking the nearest available ISD observation to the grid cell center that is located within the targeted grid cell.

Seasonality of Continental Extratropical‐Cyclone Wind Speeds Over Northeastern North America - Chen, Ting‐Chen; Di Luca, Alejandro; Winger, Katja; Laprise, René; Thériault, Julie M. (Geophysical Research Letters, 2022)
Abstract This study investigates the seasonality of near‐surface wind speeds associated with extratropical cyclones (ETCs) over northeastern North America using a global reanalysis data set during 1979–2020. As opposed to most studies that emphasize winter storms, ETCs during the fall exhibit significantly stronger 10‐m winds over this region due to the slightly stronger continental cyclones and significantly weaker low‐level stability during that time of the year. Also, ETCs favor inland lakes and Hudson Bay during the low‐ice‐content fall season, leading to lower surface roughness. Combining these results, we derive simple linear regressions to predict the 10‐m wind speed given three variables: 850‐hPa wind speed, low‐level Richardson number, and surface roughness length. This formula captures the observed seasonality and serves as a valuable tool for cyclone near‐surface wind risk assessment. , Plain Language Summary Extratropical cyclones can bring powerful winds that can cause severe damage to infrastructure. We find that cyclones with severe winds are the most frequent in the fall season over continental northeastern North America. Three reasons are found responsible: stronger continental cyclones, weaker low‐level atmospheric stability, and the lower surface roughness over lakes and Hudson Bay, where cyclones frequently occur in fall. A simple formula that can effectively assess the near‐surface wind speeds associated with cyclones is derived based on these results. , Key Points Extratropical‐cyclone‐associated 10‐m wind speeds are the strongest in the fall season over northeastern North America Besides stronger continental cyclones and 850‐hPa winds, weaker low‐level stability in fall favors stronger 10‐m wind speeds in this region Linear regression using 850‐hPa wind, Richardson number, and surface roughness well predicts cyclones' 10‐m wind speeds and seasonality